Hemodynamic Changes during Epidural Anesthesia with Various Local Anesthetics - Ye. M. Shifman; I. V. Fedulova (Общая реаниматология)
Central hemodynamic stability during gynecological laparoscopic operations remains an important problem of anes-thesiological monitoring. Subjects and methods. Fifty-eight patients who had undergone various gynecological laparoscopic operations were examined. According to the mode of anesthesia, the patients were divided into 2 groups: 1) 29 patients who received epidural anesthesia with ropivacaine; 2) 29 who had epidural anesthesia using lidocaine. The indices of cardiac performance (stroke volume, stroke index, and cardiac output), blood (diastolic, systolic, and mean) pressure, vascular parameters (linear blood flow velocity, total peripheral vascular resistance) were determined by volumetric compression oscillometry. Results. The study indicated that all the modes of anesthesia demonstrated the satisfactory condition of the cardiovascular system, but the highest stability of hemodynamic parameters was recorded in the epidural ropivacaine group. In this group, there were steady-state reductions in diastolic, systolic, mean blood pressures, and total vascular peripheral resistance and increases in stroke index, stroke volume, and linear blood flow velocity. Conclusion. Epidural anesthesia using ropivacaine during gynecological surgical endoscopic interventions is the method of analgesia causing minimal hemodynamic disorders. Key words: hemodynamics, epidural anesthesia, laparoscopic gynecological operations.